Understand How Diabetes Contributes to the Development of Kidney Disease: A Single Center Study - Rahmat Ali Khan, Mazhar Ul Haq, Muhammad Shahid, Syed Munib, Fazli Wahab (Pakistan Journal of Medical & Health Sciences, 2023)
Background: This study investigates the relationship between Diabetes and renal disease. It will review the epidemiological patterns of diabetes-related kidney disease and how various treatment choices, lifestyle changes, and expanding preventative measures might lower the risk of kidney disease in diabetics. Additionally, it will go through the symptoms and effects of kidney disease on those with Diabetes and the likelihood of effective treatment and preservation of kidney function. We’ll also discuss how this study may affect patients, healthcare professionals, and decision-makers. Methodology: From January 2022 to January 2023, this research was carried out in the nephrology department of the Miangul Abdul Haq Jahanzeb renal hospital in Swat. The study identified pertinent themes on how Diabetes leads to the development of kidney disease by using several sources, including medical papers, news articles, and web resources. The Cochrane Library and PubMed, and other pertinent research sources were examined. Additionally, qualitative interviews with healthcare experts were done, including endocrinologists, nephrologists, and other medical specialists with knowledge of Diabetes and kidney disease. Results: According to the findings, Diabetes considerably raises the risk of renal disease. Glomerulonephritis, diabetic nephropathy, and hypertension-related kidney disease accounted for most kidney conditions associated with Diabetes. Options for treatment exist to lower risk factors, control kidney disease complications, and enhance general health and well-being in people with Diabetes. The most significant lifestyle changes that people with Diabetes may do to lower their risk of kidney disease include weight reduction, regular exercise, a healthy diet, quitting smoking, and consuming less salt and alcohol. A further key role in lowering the risk of kidney disease and its development is the increased accessibility of preventative methods, such as good pre-diabetes and diabetes screening, optimal diabetes treatment, and vaccination against influenza and pneumococcal illness. Conclusion: Diabetes has a significant role in the development of renal disease. The increased accessibility of preventive screening, proper diabetes management, and immunization against infectious diseases play an important role in lowering the overall risk of developing kidney disease in people with Diabetes, even though treatment options and lifestyle changes exist to reduce risk factors for the disease’s progression. Keywords: Epidemiology, risk factors, therapy, lifestyle changes, preventive, healthcare providers, pre-diabetes screening, diabetes management, vaccination, renal disease